(untitled) (Research, Society and Development, 2022)
Falls are a concern for society and government agencies as they are directly related to the health of the elderly population. Enabling and carrying out interventions with the elderly can minimize the problems of falls, pathologies associated with falls and delay functional decline. The aim of the study was to investigate which interventions and physical interventions were performed in elderly people with a history of falls. The literature search was carried out from 2008 to 2022 in the Scientific Electronic Library Online (SCIELO), National Library of Medicine (PUBMED) and Excerpta medica dataBASE (EMBASE) databases. Articles that performed interventions with physical exercises aimed at reducing falls and improving health were included. A search strategy resulted in 237 articles these 10 were included for final analysis. Most of the articles included had positive results in reducing the risk of falls, especially those that prioritized balance and muscle strength components. Studies have stimulated the improvement of physical, functional, cognitive, learning and motor behavior, postural stability, modification of neurophysiological parameters and environmental changes, proposing health promotion and improvement of physical fitness. However, due to the importance of the topic, further studies on physical exercises performed by elderly fallers are suggested.